Factors of the spread of the phenomenon Of abuse of power - Abdurrahman Medjdoub (مجلة الاجتهاد للدراسات القانونية والاقتصادية)
Abuse of power represents, in general, all the attempts made by managers and employees, by which they place their illegitimate private interest above the public interest, bypassing the values they are committed to respecting. Abuse of power is a violation of public duty, a departure from moral standards in work, and therefore illegal and unethical behavior. Several factors play an important role in the spread of the phenomenon of abuse of power in society. There are administrative and economic factors, as well as social and legal factors.